ijee 2022
DOI: 10.48165/ijee.2022.58413
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Fisheries and Management- Insights from Dal Lake, Kashmir

Abstract: The present study was done during 2019-20 to assess the current fisheries status of Dal lake in terms of species diversity, trophic status, trends and patterns in fish catch, the lake’s physicochemical properties and its management. Shannon-Wiener index used to calculate the species diversity was 2.08 with the species evenness value of 2.19. The water quality analysis revealed that the lake is highly polluted due to various anthropogenic activities like sewage influx, vegetable cultivation, tourism activities,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…The findings of the study are in line with works reported by Kamaruddin and Samsudin (2014), Datta et al (2017), Barela et al (2018), Girish et al (2020), Mishra and Debata (2021), Mir et al (2023), Manikanta and Satpathy (2023) and Gautam and Jha (2023), Patel et al, 2023, Sangpuii andMalhotra (2016). These studies opined that Livelihoods Indices are useful tool in assessing the livelihood elements of the rural poor households with special reference to tribal farmers.…”
Section: Comparison Of Components Of Livelihood Endowment Status (Les...supporting
confidence: 89%
“…The findings of the study are in line with works reported by Kamaruddin and Samsudin (2014), Datta et al (2017), Barela et al (2018), Girish et al (2020), Mishra and Debata (2021), Mir et al (2023), Manikanta and Satpathy (2023) and Gautam and Jha (2023), Patel et al, 2023, Sangpuii andMalhotra (2016). These studies opined that Livelihoods Indices are useful tool in assessing the livelihood elements of the rural poor households with special reference to tribal farmers.…”
Section: Comparison Of Components Of Livelihood Endowment Status (Les...supporting
confidence: 89%
“…The J&K State Department of Fisheries (DoF), J&K State Department of Tourism (DoT), J&K Lake Conservation and Management Authority (JKLCMA), fishers, and people living on the lake periphery are involved to manage various facets of the lake. The primary issues with the fisheries components of the lake are the lack of cooperation between DoF and other departments and the lower priority given to fisheries activities because of their minimal financial contribution to the state (Mir et al, 2022).The creation of alternative livelihoods to decongest the lake should focus on the abilities of the fishers, such as cage culture, ornamental fish culture/rearing, aquarium manufacturing, and aqua-based ecotourism, and the fishers should be given suitable marketing facilities. Also, strict enforcement of laws preventing the flow of civic discharge into the lake by improving the already established STPs and developing new ones.…”
Section: Suggestive Measuresmentioning
confidence: 99%
“…Over the last two decades, the Sustainable Livelihoods Approach (SLA) globally played an essential role in framing and informing the debate on sustainable livelihoods and in analysing what enables and inhibits resilient and sustainable small-scale fisheries (Allison & Ellis, 2001;Andrew et al, 2007;Serrat, 2017). The fisher folk of Kashmir valley is the marginalized section of the society, which are prone to various shocks and seasonality trend cause of their poor socio-economic conditions (Mir et al, 2022), more sensitivity, and less adaptive capacity. For instance, the fisherfolk in the Kashmir valley were severely impacted by the massive fish stock mortality that resulted from the flood in 2014, which had disastrous effects on fish variety.…”
Section: Introductionmentioning
confidence: 99%
“…And is often referred as the "Jewel in the crown of Kashmir" or "liquid heart" due to its fame as a popular tourist attraction (Masoodi and Kundangar, 2018). The lake is a vital source of income for local inhabitants involved in tourism, fishing, and agriculture (Mir et al, 2022). However, in the past four decades, there has been a drastic change in the water quality of the lake (Kumar et al, 2022) due to many anthropogenic activities like the continuous influx of untreated sewage, agricultural and surface runoff (Khan and Ansari, 2005;Zargar et al, 2012;(Rashid et al, 2017;Mushtaq et al, 2018;Kumar et al, 2022) is posing a threat to the aquatic ecology of the lake Ganaie and Hashia (2020).…”
Section: Introductionmentioning
confidence: 99%